Kebili workshop: Enhancing utilization of local fodder resources - Mannai, Amal; Moujahed, Nizar; Frija, Aymen (International Center for Agricultural Research in the Dry Areas, 2023)
The photo illustrates a two-day workshop in Kebili focused on developing local forage resources, particularly date palm by-products. The first day involved visits to six units producing ruminant feed from date palm by-products. The second day featured a presentation on local food resource utilization, which gathered 56 stakeholders, including scientists, local extension agents, private sector representatives, research, and development institutions, and thirty farmers (including five women).